A General Composite Algorithms for Solving General Equilibrium Problems and Fixed Point Problems in Hilbert Spaces. (12th May 2011) - Wangkeeree, Rattanaporn; Kamraksa, Uthai; Wangkeeree, Rabian
Abstract : We introduce a general composite algorithm for finding a common element of the set of solutions of a general equilibrium problem and the common fixed point set of a finite family of asymptotically nonexpansive mappings in the framework of Hilbert spaces. Strong convergence of such iterative scheme is obtained which solving some variational inequalities for a strongly monotone and strictly pseudocontractive mapping. Our results extend the corresponding recent results of Yao and Liou (2010).